TNFAIP3 gene rs7749323 polymorphism is associated with late onset myasthenia gravis. Issue 20 (May 2017) - Yang, Hong-Wei; Xie, Yanchen; Zhao, Yuan; Sun, Liang; Zhu, Xiaoquan; Wang, Shuhui; Zhang, Yong-Qiang; Lei, Ping; Meng, Yunxiao
Abstract : Abstract: In this study, we intended to genotype 2 single nucleotide polymorphisms (SNPs) of tumor necrosis factor α-induced protein 3 ( TNFAIP3 ) genes and explore an association of TNFAIP3 genetic polymorphism with the patients of myasthenia gravis (MG) at clinical level. In brief, 215 of adult MG patients were divided into subgroups according to their clinical features, age of onset, thymic pathology, and autoantibodies. Two hundred thirty-five of healthy controls were also divided into subgroups with gender- and age-matched. The allele and genotype frequencies of subgrouped patients were found to be higher than those of healthy controls. The distribution of TNFAIP3 gene rs7749323*A allele of late onset MG (LOMG, with positive acetylcholine receptor antibody and without thymoma) subgrouped patients was also significantly higher than that of gender- and age-matched healthy controls (7.4% vs 2.4%, odds ratio [OR] = 3.27, 95% confidence interval [CI] 1.01–10.6, P  = .04). Furthermore, analysis to the genotype frequencies indicates that the carriers of rs7749323*A allele of LOMG group became more frequent than that of age-matched healthy controls (14.9% vs 4.8%, OR = 3.47, 95% CI 1.04–11.6, dominant model: P  = .03). It is interesting to notice that there is no significant association between the rs7749323 and susceptibility of other MG subgroups. Therefore, it is suggested that the SNPs in the 3′ flanking region (rs7749323) of TNFAIP3 gene and the genetic variations of TNFAIP3 gene may take an important role in the susceptibility of LOMG.